Therapeutic strategies for infections by klebsiella pneumoniae carbapenem resistant: a narrative review (Research, Society and Development, 2022)
Currently, bacterial infections with resistance patterns have been a major problem to be fought. In this scenario, the bacterium Klebsiella pneumoniae presents great importance due to its profile of multidrug resistance to antimicrobial drugs, through the production of enzymes with hydrolytic character, called carbapenemases. Because of this, it is necessary that the therapeutic protocols be reviewed for the satisfactory clinical evolution of patients, where knowing the pathogen's mechanisms of infection and its morphological characteristics elucidate which is the adequate therapeutic strategy. Thus, the objective of this work is to survey the literature on therapeutic strategies in infections by carbapenemase-producing K. pneumoniae, aiming at an analysis of the possibilities of treatment, comparing their benefits, weaknesses and possible impacts, as well as the application of new drugs in this theme. For this, a narrative bibliographic review was carried out, outlined by the search of articles, books and dissertations in the main electronic repositories. The descriptors used were: klebsiella pneumoniae carbapenemase; KPC-producing enterobacteriae; KPC-KP pathogenesis; KPC-KP laboratory diagnosis; Klebsiella pneumoniae treatment and health teaching. Finally, it was possible to observe that among the therapies used in infections by Klebsiella pneumoniae resistant to carbapenems, monotherapy tends to be ineffective, since this bacterium is multidrug resistant to conventional antimicrobial drugs. The use of combination therapy is more effective, due to the combined activity of the drugs in question. However, it is necessary that the physiological conditions of each patient be evaluated, given the high nephrotoxicity of some antimicrobials. As an addendum, new drugs also demonstrate significant efficacy for these infections.